Search for heavy neutral Higgs bosons produced in association with b-quarks and decaying into b-quarks at √s=13TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; et al. (Physical review, 2020)
A search for heavy neutral Higgs bosons produced in association with one or two b-quarks and decaying to b-quark pairs is presented using 27.8 fb−1 of √s=13 TeV proton-proton collision data recorded by the ATLAS detector at the Large Hadron Collider during 2015 and 2016. No evidence of a signal is found. Upper limits on the heavy neutral Higgs boson production cross section times its branching ratio to b¯b are set, ranging from 4.0 to 0.6 pb at 95% confidence level over a Higgs boson mass range of 450 to 1400 GeV. Results are interpreted within the two-Higgs-doublet model and the minimal supersymmetric Standard Model.
ATLAS collaboration: G. Aad, C. Anders, G.V. Andrei, C. Antel, A. Bolz, O. Brandt, M. Dunford, D.E. Feirreira de Lima, S. Franchino, M.P. Geisler, L. helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, P. Ott, M. Sahinsoy, A. Schöning, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, L. Vigani, J. Wang, S. Weber, M. Wessels, X. Yue [und viele weitere]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 03.11.2020